2010
DOI: 10.1029/2009jd012574
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of simulated precipitation over East Asia in two regional climate models

Abstract: [1] The diurnal variations of precipitation over East Asia simulated by the National Centers for Environmental Prediction (NCEP) Regional Spectral Model (RSM) and the Weather Research and Forecasting (WRF) model are evaluated during the integration period of June-July-August (JJA) 2006. The models reproduce the observed seasonal mean of large-scale features and precipitation satisfactorily, although the bias patterns differ in both models. The lower tropospheric circulation features are better reproduced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 63 publications
6
65
1
Order By: Relevance
“…This model has been widely evaluated over East Asia and produced successful results in reproducing summer monsoon precipitation over the region (Yhang and Hong, 2008;Kanamitsu et al, 2010). It has been employed as a useful research tool in understanding precipitation mechanisms embedded within the East Asian monsoon (Kang and Hong, 2008;Koo and Hong, 2010). Figure 1 shows the simulation domain of the RSM, which is the CORDEX East Asian domain with a horizontal grid spacing of approximately 50 km (0.44 degrees).…”
Section: Experimental Designmentioning
confidence: 99%
“…This model has been widely evaluated over East Asia and produced successful results in reproducing summer monsoon precipitation over the region (Yhang and Hong, 2008;Kanamitsu et al, 2010). It has been employed as a useful research tool in understanding precipitation mechanisms embedded within the East Asian monsoon (Kang and Hong, 2008;Koo and Hong, 2010). Figure 1 shows the simulation domain of the RSM, which is the CORDEX East Asian domain with a horizontal grid spacing of approximately 50 km (0.44 degrees).…”
Section: Experimental Designmentioning
confidence: 99%
“…In general, the literature points toward problems in the boundary layer and convective parameterizations (Wang et al 2007;Koo and Hong 2010), inadequate grid resolution (Lee et al 2007b), error in precipitation generation (Gianotti et al 2012), and error in peak precipitation time as compared with the observations (Joseph et al 2008). Most of these studies involved RCMs and did not make use of high-resolution datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2007) investigated the effect of lateral convective entrainment-detrainment rates on a simulated diurnal cycle of precipitation. Koo and Hong (2010) investigated diurnal variability and showed that cumulus parameterization modulates the simulated timing of maximum precipitation over land. Qian (2008) simulated the diurnal precipitation cycle over Java, Indonesia and showed that the model was able to reproduce the diurnal cycle, but the simulation was restricted to a single island, and thus the results could not be extended to the rest of the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not only of hydrological, but also of geomorphological significance, because heavy precipitation moulds (transforms) slopes in the catchments of closed basins [32]. Having a detailed record of the distribution of effective precipitation (measurement every half an hour), it is possible to determine the amount of rainwater that appears on the surface of the catchment at any given time interval and that enters further stages of the water cycle in nature [33].…”
Section: Resultsmentioning
confidence: 99%